Cutaneous Vasculi̇ti̇s - Ertürk, Adem (General Internal Medicine V, 2023)
Vasculitis is a disease characterized by thinning of the vessel wall and narrowing or occlusion of the vessel lumen due to cells that inflame the vessel wall. The vessel wall becomes thinner, vessel permeability increases, and rupture occurs in the vessel wall. The prevalence of skin involvement is high in vasculitis. Vasculitides in which skin involvement is more prominent than systemic involvement are called cutaneous vasculitides. Cutaneous vasculitis typically involves the dermal and subcutaneous vessels of small or medium size. The clinical and pathological observations of vasculitis are dependent upon the size of the damaged blood vessels and the specific site of involvement. While palpable purpura is the most frequently observed clinical manifestation of vasculitis, other cutaneous lesions such as infiltrative erythema, purpura, purpuric papules, petechiae, urticaria, livedo reticularis, nodules, hemorrhagic bullae and vesicles, digital gangrene, deep ulcers, and may also be present. The visibility and accessibility of the skin as an organ present notable advantages in terms of disease detection and early diagnosis, as it allows for both physical assessment and biopsy procedures. Since the skin lesions in systemic and cutaneous vasculitis show similar clinical and pathological features, systemic involvement should be investigated in detail before diagnosing cutaneous vasculitis.